Influence of abiotic stress signals on secondary metabolites in plants - Ramakrishna, Akula (Landes Bioscience, 2011)
Plant secondary metabolites are unique sources for pharmaceuticals, food additives, flavors, and industrially important biochemicals. Accumulation of such metabolites often occurs in plants subjected to stresses including various elicitors or signal molecules. Secondary metabolites play a major role in the adaptation of plants to the environment and in overcoming stress conditions. Environmental factors viz. temperature, humidity, light intensity, the supply of water, minerals, and CO(2) influence the growth of a plant and secondary metabolite production. Drought, high salinity, and freezing temperatures are environmental conditions that cause adverse effects on the growth of plants and the productivity of crops. Plant cell culture technologies have been effective tools for both studying and producing plant secondary metabolites under in vitro conditions and for plant improvement. This brief review summarizes the influence of different abiotic factors include salt, drought, light, heavy metals, frost etc. on secondary metabolites in plants. The focus of the present review is the influence of abiotic factors on secondary metabolite production and some of important plant pharmaceuticals. Also, we describe the results of in vitro cultures and production of some important secondary metabolites obtained in our laboratory.